2019
DOI: 10.26750/vol(6).no(1).paper9
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of FDI Inflows and Outflows on Economic Growth: An Empirical Study of some Developed and Developing Countries

Abstract: FDI is an investment including a long-term relationship and reflecting a lasting interest and control of a resident entity in one economy. FDI is a combination of capital, technology, marketing and management. Based on the Neoclassical, Exogenous and modern theories FDI has a positive role in accelerating economic growth and development. Many countries are improving their economy in order to attract FDI.  The main objective of this study is to examine the impact of FDI inflows and outflows on economic gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
(2 reference statements)
2
3
0
Order By: Relevance
“…In the short-run, however, the result shows that there is a positive relationship between outward FDI and economic growth, with an estimated coefficient value of 0.109 and one that was statistically significant at the 10 per cent level. This result affirmed the findings of Herzer (2010), Chen (2018), Ahmed and Ibrahim (2019), and Amin et al (2020), who observed that outward FDI boosted economic growth over the short-run. This finding also revealed that outward FDI can be used by domestic businesses to expand into new international markets and import cheaper inputs from the host country, allowing them to Sadiq, 2013;Knoerich, 2017;Amin, et al, 2020).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In the short-run, however, the result shows that there is a positive relationship between outward FDI and economic growth, with an estimated coefficient value of 0.109 and one that was statistically significant at the 10 per cent level. This result affirmed the findings of Herzer (2010), Chen (2018), Ahmed and Ibrahim (2019), and Amin et al (2020), who observed that outward FDI boosted economic growth over the short-run. This finding also revealed that outward FDI can be used by domestic businesses to expand into new international markets and import cheaper inputs from the host country, allowing them to Sadiq, 2013;Knoerich, 2017;Amin, et al, 2020).…”
Section: Resultssupporting
confidence: 89%
“…Furthermore, Amin et al (2020) offered compelling evidence that outward FDI has a favourable and significant impact on Romania's economic growth, with the increase in outward FDI having a higher impact. Commonly, the studied literature has a gap in that some studies only looked at the influence of outward FDI on economic growth in developed countries (Lee, 2010;Herzer, 2010); others only looked at developing ones (Chen and Zulkifli, 2012;Wong, 2013;Al-Shawaf and Almsafir, 2016;Basar and Özkilbaç, 2016;Ameer et al, 2017;Lee and Sermcheep, 2017;Chen, 2018;Ahmed and Ibrahim, 2019;Mohanthy and Sethi, 2019;Amin et al, 2020;Obobisa et al, 2021). However, studies evaluating the impact of outward FDI on economic growth in ASEAN is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…The negative coefficient sign of the exchange rate with Iraq' s GDP is in parallel with previous studies )see, i.e. Ahmed andIbrahim, 2019 Saud et al, 2021(. Moreover, the coefficient sign of a dummy variable of the global financial crisis )GFC( is also negative and statistically insignificant.…”
Section: Cusum-squared Stablesupporting
confidence: 83%
“…Yonus, Roshna (2019) 6 examined and analyse the impact of FDI inflows and outflows on the economic growth and find that inflow and outflow has positive impact on US & UK economy and inflow has negative impact on France economy and Malaysia, Turkey and Iran economies have positive impact of inflows and outflows.…”
Section: Review Of Literaturementioning
confidence: 99%